RELASI MASYARAKAT DENGAN HUTAN (TINJAUAN TENTANG UPAYA YANG DILAKUKAN MASYARAKAT DALAM MEMPERTAHANKAN KEBERADAAN HUTAN MANGROVE) - Trisni Andayani, dkk (JURNAL KELUARGA SEHAT SEJAHTERA, 2014)
ABSTRACT Mangrove forest is an ecosystem having an important role in terms of the ecological and socio-economic aspects. Mangrove forest is a forest type grown with mangrove trees (mangrove) located along the coast or the river estuary and influenced by the tide. Mangrove forests have multiple functions and it is a very important link in preserving the balance of the biological cycle in the waterworks. Mangrove forests are important for traditional fishermen and citizen living in the Jaring Halus village. In addition to save their lives from the threat of coastal abrasion. Mangrove forest areas also contribute to their economy. Fish, shrimp, scallops ,crabs , and other organisms make mangrove region as an area of care (nursery ground), the area to spawn ( spawning ground ) , and areas for foraging (feeding ground). It shows a very high level of dependence for the aquatic biota. If in terms of social and economic aspects of the area is also very influential on the development of human life living in the vicinity. From the economic aspect, mangrove forests can be developed into tourism forest giving the positive impact directly on the lives of people around the Jaring Halus village. Kata Kunci : Hutan mangrove, masyarakat, relasi.